Plant signaling networks involving Ca2+ and Rboh/Nox-mediated ROS production under salinity stress - Kurusu, Takamitsu; Kuchitsu, Kazuyuki; Tada, Yuichi (Frontiers in Plant Science, 2015)
Salinity stress, which induces both ionic and osmotic damage, impairs plant growth and causes severe reductions in crop yield. Plants are equipped with defense responses against salinity stress such as regulation of ion transport including Na+ and K+, accumulation of compatible solutes and stress-related gene expression. The initial Ca2+ influx mediated by plasma membrane ion channels has been suggested to be crucial for the adaptive signaling. NADPH oxidase (Nox)-mediated deliberate production of reactive oxygen species (ROS) has also been suggested to play crucial roles in regulating adaptation to salinity stress in several plant species including halophytes. Respiratory burst oxidase homolog (Rboh) proteins show the ROS-producing Nox activity, which are synergistically activated by the binding of Ca2+ to EF-hand motifs as well as Ca2+-dependent phosphorylation. We herein review molecular identity, structural features and roles of the Ca2+-permeable channels involved in early salinity and osmotic signaling, and comparatively discuss the interrelationships among spatiotemporal dynamic changes in cytosolic concentrations of free Ca2+, Rboh-mediated ROS production, and downstream signaling events during salinity adaptation in planta.